A case Report of Perforated Primary Follicular Lymphoma of the Jejunum presenting as Aneurismal Form - Thomas Marcel Mbar Wade; Linda Bentefouet; Pape Abdoulaye Ba; Mohamed Lamine Diao; Adama Berthe; Ibrahima Konaté (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Primary Gastrointestinal Follicular Lymphoma is very rare. It is considered as an indolent lymphoma, but a complication such as a perforation can increase the morbidity and mortality. We report the case of a 57-years-old man who had a perforation primary follicular lymphoma of the jejunum presenting as aneurismal form. He had peritonitis at his admission, and his abdominal CT revealed a massive pneumoperitoneum and a segmental dilatation of the small intestine.